Formazan ring method: a simple test for screening of glucoce-6-phosphate dehydrogenase (G-6-PD) deficiency in the neonates - Purnomo Suryantoro, Purnomo Suryantoro (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
Glucose-6-phosphate dehydrogenase deficiency, is an x-linked inherited disease which is responsible for episodic hemolytic anemia. The incidence correlates with the malarial epidemic in many area like Mediterranean, Africa and Asia including South East Asia.This paper reports a simple, cheap, traumatic, and reliable method screening test called formazan ring developed by Nishiyama. Among 145 new-born infants in this report the low enzyme activity was as high as 9(6.2%) Including 2(1.4%) G-6-PD deficiency.Key words: glucose-6-phosphate dehydrogenase deficiency - x-linked inherited disease - formazan ring test - neonatal screening